Should I get rid of my monophasic defibrillator? – An exercise of Evidence Based Medicine - Pazin-Filho, Antonio (Medicina (Ribeirao Preto), 2010)
Appropriate interpretation of literature is an ability that every physician should be apt. This article will provide guidelines for this interpretation, providing fundamental concepts contextualized in a practical example.